Development Strategy of Early Childhood Education Institutions Through IFAS and EFAS Matrix Analysis (Study on Kindergarten Unit of PASBQ Gontor) - Dhika Amalia Kurniawan; Rohman Alim (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
The Kindergarten Unit of Pesantren Anak Sholeh Baitul Qur'an (PASBQ) is a full-day school system kindergarten educational institution located in Ponorogo Regency. Pesantren Anak Sholeh aims to develop pupils with good character so they can become so and sholehah children from an early age. It offers religious and general education to its students. The goal of this research is to uphold PASBQ's vision and mission while enabling the organization to compete with Ponorogo's 19 top kindergartens. This study employs a qualitative, descriptive research design. Data was gathered by researchers using field observation, document-based data gathering, unstructured interviews, and triangulation. This study used IFAS and EFAS Matrix Analysis to gather data on the development strategy of early childhood education institutions (Case Study at Kindergarten Unit of Pesantren Anak Sholeh Baitul Qur'an). Based on the research findings from the Kindergarten Unit of Pesantren Anak Sholeh Baitul Qur'an Ponorogo, the researcher has come to the conclusion that an aggressive strategy is the best course of action for development. This strategy entails maximizing already-existing opportunities and strengths while upholding the standard of instruction in order to stay ahead of other educational institutions. The following are some of the development outcomes: Adding buildings for classrooms and teachers' rooms, Improving the quality of PASBQ education.